Foto-Etnografi dalam Proses Penciptaan Karya Seni Fotografi - Arief Datoem (PANGGUNG, 2013)
ABSTRACT This article aims at deepening the possibility of utilizing the art of photography that is rich of sig- nificance of the socio-cultural representation. The visual ethnographic field or photo-ethnography, which is relatively new, can provide assistance and answer for this. Therefore, the author has tried a form of collaboration between the photo-ethnographic approach and the sense approach in doing his research on the subject in order to obtain the deep understanding and the truth significance attached to them. The method of digital photography art creation which is intuitively the basis of the art cre- ation in digital domain, then was tried to be formulated, based on heuristics research in the process of the art of digital photography. This concept was developed from the experience in the field of digital photography and visual anthropology, guided by the basic theories of creativity, quantum theory in art, and theory of artistic creation that has existed before. Through emotional approach as a method, along with the structured systematic approach of photo-ethnography and with the deep awareness of the environment and social life of the subject leads to the creation of the image that tends to be better and more meaningful, more productive in a social sense, and offers a credible empiric documentation. Keywords: photo-ethnography, photography art works  ABSTRAK Artikel ini dibuat dalam upaya melakukan pendalaman mengenai kemungkinan peman- faatan seni fotografi yang kaya makna representasi sosio-kultural. Bidang etnografi visual atau foto-etnografi yang relatif masih baru, dapat memberikan bantuan dan jawaban un- tuk hal ini. Oleh karena itu penulis mencoba suatu bentuk kolaborasi antara pendekatan foto-etnografi dengan pendekatan rasa ketika melakukan penelitian terhadap subjek agar diperoleh pemahaman mendalam serta makna kebenaran yang menyertainya. Metode penciptaan seni fotografi digital yang merupakan dasar dari penciptaan seni secara intu- itif dalam domain digital, kemudian dicoba dirumuskan, berdasarkan penelaahan heu- ristik dalam proses seni fotografi digital. Konsep ini dikembangkan dari pengalaman di bidang fotografi digital dan antropologi visual, dipandu oleh teori-teori dasar kreativitas, teori kuantum dalam seni, dan teori penciptaan seni yang telah ada sebelumnya. Melalui pendekatan emosional sebagai metode, disertai dengan pendekatan sistematis yang ter- struktur dari foto-etnografi dan dengan kesadaran yang mendalam mengenai lingkungan dan kehidupan sosial subjek mengarah pada penciptaan gambaran yang cenderung lebih baik dan lebih bermakna, lebih produktif dalam arti sosial, dan menawarkan dokumentasi empiris yang kredibel. Kata kunci: foto-etnografi, karya seni fotografi